Kualitas Layanan Aspirasi dan Pengaduan Online Rakyat (Lapor Pak Yes!) di Dinas Komunikasi dan Informatika Kabupaten Lamongan - Nasywa Rahmadhanty Tiaranita; Trenda Aktiva Oktariyanda; Meirinawati M; Eva Hany Fanida (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study examines the quality of the Online Public Aspiration and Complaint Service (LAPOR PAK YES!) managed by the Communication and Informatics Office of Lamongan Regency as a form of digital-based public service innovation. The platform is intended to facilitate public participation by enabling citizens to submit aspirations, complaints, and reports regarding public services. This research employs a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The analysis is guided by the E-ServQual framework, which includes efficiency, system reliability, fulfillment, privacy, responsiveness, compensation, and contact dimensions. The findings reveal that the LAPOR PAK YES! service generally demonstrates adequate service quality, particularly in terms of ease of use and accessibility. However, several challenges remain, including limited public awareness due to insufficient direct socialization, delays in follow-up responses, and dependency on coordination with relevant agencies for complaint resolution. As a result, some reports are formally processed but lack timely and clear outcomes for users. This condition indicates a gap between public expectations and service performance. Therefore, this study recommends strengthening cross-agency coordination, improving response timeliness, and expanding outreach efforts to enhance public awareness and trust. These measures are essential to ensure more responsive, transparent, and participatory digital public services at the local government level.